PMO Growth Path: From Project Execution to Organizational Impact - Alin Veronika (Journal of Project Management Research, 2025)
Over the past two decades, the Project Management Office (PMO) has become a common organizational structure across industries. Organizations increasingly rely on projects as a primary mechanism to implement strategy, drive innovation, and manage complex change initiatives. This growing reliance on projects—often referred to as projectification—has led organizations to establish institutional structures capable of coordinating project activities and ensuring governance across portfolios (Wagner et al., 2026). Within this context, PMOs have emerged as organizational entities responsible for centralizing, coordinating, and supporting project management practices across an organization. They provide governance mechanisms, methodological standards, and operational support to ensure that projects are executed effectively and consistently. However, despite their widespread adoption, many PMOs struggle to demonstrate their strategic contribution to the organization. In practice, PMOs are often perceived primarily as administrative or reporting functions focused on compliance, documentation, and project monitoring. While these roles are important for maintaining operational discipline, they rarely translate into visible organizational impact.